Estimating and forecasting conditional risk measures with extreme value theory: A review - Marco Bee; Luca Trapin (Risks, 2018)
One of the key components of financial risk management is risk measurement. This typically requires modeling, estimating and forecasting tail-related quantities of the asset returns' conditional distribution. Recent advances in the financial econometrics literature have developed several models based on Extreme Value Theory (EVT) to carry out these tasks. The purpose of this paper is to review these methods.
Keywords: 330; Extreme Value Theory; volatility; risk; quantile